Evaluation of BRAF, RAS, RET/PTC, and PAX8/PPARg alterations in different Bethesda diagnostic categories: A multicentric prospective study on the validity of the 7‐gene panel test in 1172 thyroid FNAs deriving from different hospitals in South Italy. Issue 2 (10th December 2019) - Bellevicine, Claudio; Migliatico, Ilaria; Sgariglia, Roberta; Nacchio, Mariantonia; Vigliar, Elena; Pisapia, Pasquale; Iaccarino, Antonino; Bruzzese, Dario; Fonderico, Francesco; Salvatore, Domenico; Biondi, Bernadette; Masone, Stefania; et al.
Abstract : Background: Thyroid fine‐needle aspiration (FNA) is a reliable and cost‐effective diagnostic tool for establishing the nature of thyroid nodules, although up to 30% of FNAs are still classified as "indeterminate." Molecular testing of FNAs could improve preoperative diagnosis, thereby reducing unnecessary surgery. In this multicenter prospective study the authors investigated,  using a 7‐gene assay, the distribution and diagnostic impact of BRAF, RAS, RET/PTC, and PAX8/PPARg, the most frequent genomic alterations occurring during thyroid oncogenesis. Methods: In total, of 1172 routine FNAs from 7 centers in southern Italy were classified according to the Bethesda System for Reporting Thyroid Cytopathology. Each specimen was tested, and molecular data were compared with available histology or cytologic follow‐up. Results: In particular, for atypia of undetermined significance/follicular lesion of undetermined significance cases, the 7‐gene test confirmed the high positive predictive value of BRAF V600E and BRAF ‐like mutations (80%) and the moderate positive predictive value of RAS ‐like alterations (32.4%), suggesting different surgical management, depending on the type of mutation. The rate of mutation‐positive FNAs was strictly related to the risk of malignancy of each diagnostic class, supporting the identification of prognostically relevant diagnostic categories. Conclusions: The 7‐gene panel test improves the preoperative risk stratification of indeterminate thyroid FNAs, especially when considering the biologic significance of the different types of mutations. Moreover, the rate of mutation‐positive FNAs is related to the risk of malignancy of each diagnostic class. Abstract : The 7‐gene panel test improves the preoperative risk stratification of indeterminate thyroid fine‐needle aspirations, especially when considering the biologic significance of the different types of mutations (ie, BRAF ‐like and RAS ‐like alterations). Moreover, the rate of mutation‐positive thyroid fine‐needle aspirations is related to the risk of malignancy of each diagnostic class, supporting the establishment, from a molecular standpoint, of prognostically relevant cytologic diagnostic categories.